Liberia : Can Employment Opportunities Help Build Peace? - World Bank (Washington, DC, 2015)
Whats the most effective way to reintegrate ex-combatants and reduce illegal activities? This policy note reviews an innovative program that had a big impact. In Liberia, where civil wars were fought on and off between 1989 and 2003, the non-profit organization, action on armed violence, the Government of Liberia, and the United Nations developed an innovative program to help ex-combatants move into full-time farm work by giving them training, counseling, and start-up capital. The evaluation found that the program successfully shifted high-risk men from criminal activities into farming. The evaluation also showed that skills training arent always enough. As policy makers in the region look to strengthen their economies and boost stability, the results of this evaluation offer guidelines for crafting successful programs. These findings will likely help development experts to create programs that help the millions of young people entering the labor force find meaningful and productive work. This Evidence to Policy note was jointly produced by the World Bank Group, the Strategic Impact Evaluation Fund (SIEF), and the British governments Department for International Development.